France and Germany Nuclear Energy Policies Revisited: A Veblenian Appraisal - Petit, Pascal (Panoeconomicus, 2013)
Nuclear energy policy should have been a major area of cooperation for France and Germany, playing a lead role in the energy policy of the EU. Yet they have retained different options, especially regarding nuclear energy while the EU energy policy remained very indicative. These two “coordinated economies” should have been able to cooperate more closely on this issue. While the reasons for this difference in behavior have much to do with the specificities of the nuclear energy, they are more precisely related to the continuously rising level of security requirements, a learning process in which the magnitude of risks and time lengths appeared, even before Fukushima, to go beyond rational boundaries on which cooperation (as well as market) ventures could be based. This raises the issue in the present state of the technologies of the possibility of an international governance of this nuclear industry. Key words: Nuclear energy, Coordinated economy, European Union, Energy transition. JEL: N70.